Effect of TLR4/MyD88 Signaling Pathway on Expression of IL-1β and TNF-α in Synovial Fibroblasts from Temporomandibular Joint Exposed to Lipopolysaccharide - Xuefen Lin; Jingjing Kong; Qingting Wu; Yingying Yang; Ping Ji (Mediators of Inflammation)
Accumulating evidence from previous studies suggested that interleukin-1 (IL-1β) and tumor necrosis factor-α (TNF-α) play an important role in pathogenesis of temporomandibular disorders (TMD). However, the cell surface receptors and the intracellular signal pathways leading to these cytokines expression are not fully understood. In the current study, we investigated the roles of Toll-like receptor 4 (TLR4) and its adaptor myeloid differentiation factor 88 (MyD88) in the expression of IL-1β and TNF-α in synovial fibroblasts (SFs) separated from rat temporomandibular joint (TMJ) with lipopolysaccharide (LPS) stimulation. The results showed that treatment with LPS could increase TLR4, MyD88, IL-1β, and TNF-α expression at both mRNA and protein levels. In addition, increased expression of IL-1β and TNF-α could be blocked by treatment with TAK-242, a blocker of TLR4 signaling, and also by MyD88 inhibitory peptide (MIP). These findings suggested that maybe TLR4/MyD88 signal transduction pathway participates in enhanced expression of IL-1 and TNF-α in patients with TMD. The activation of TLR4/MyD88 signal transduction pathway which results in production of proinflammatory factors may play a role in the pathogenesis of TMD.